THE NEED ASSESSMENT FOR IMPROVING THE COMPETENCE OF THAI TEACHERS IN THE MEASUREMENT AND EVALUATION OF ANALYTICAL THINKING - Klaharn, Rungrudee (PUPIL: International Journal of Teaching, Education and Learning, 2017)
The needs assessment is the process for determining and addressing needs. It is gaps between current conditions and desired conditions. It is the process of collecting information about a competency need that could be met by conducting training. The needs assessment process helps the person requesting training to specify the training need.The objectives of this research were: 1) to study the needs and reality competence of Thai teachers to improve the competence in the measurement and evaluation of analytical thinking, 2) to prioritize the needs to improve Thai teachers competence in measurement and evaluation of analytical thinking. The research was undertaken by using a need assessment research that consisted of 2 steps including the conceptual research framework, and the need assessment to improve the competence in the measurement and evaluation of analytical thinking. The samples were 440 teachers from 4 regions and Bangkok Metropolitan selected by the multi-stage random sampling. The research instrument was a three rating scale about teachers competency using the dual-response format. The reliability coefficients of questionnaire ranges from .93-.97. The data obtained were analyzed by using the arithmetic mean and the standard deviation. The needs assessments were assessed by the Modified Priority Needs Index (PNImodified) compared with the average by paired samples t-test.The research finding were: 1) The degree of need competence of Thai teachers competence in measurement and evaluation of analytical thinking including the overall average was high (mean = 2.91, S.D. = .66) and the degree of reality competence of Thai teachers competence in measurement and evaluation of analytical thinking including all aspects of the overall average was medium (mean = 2.03, S.D. = .30). A significant difference was found between the need competence and the reality competence of Thai teachers to improve competence in measurement and evaluation of analytical thinking, 2) Thai teachers competence in measurement and evaluation of analytical thinking of the samples were essential requirements for all items with the PNI modified between 0.40 to 0.48. In the future, based on this research, the training curriculum will be developed for the Thai teachers to improve the competence in the measurement and the evaluation of analytical thinking.